The effectiveness of e-word-of-mouth communication about smartphones purchase intention: digital influencer - Rosário, J. F. do; Loureiro, S. M. C. (International Journal of Internet Marketing and Advertising, 2021)
This study aims to compare the effectiveness of eWOM on Facebook, Instagram and YouTube for smartphone buying decision, provided by digital influencers. For such, a quantitative methodology was adopted using three online questionnaires (one for each social media platform), to be answered by Portuguese adults who use them. This comparison has foundation on the IACM, a model introduced by Erkan and Evans to explore the influence of eWOM on consumer's buying intentions. The results show that, while the eWOM information from digital influencers about smartphones has a global consumer receptivity in the three social media platforms considered, that is not happening in a very assertive way for some items [average not greater than 3 (Likert scale 1-5)], in a significant statistically way. The research also demonstrate that YouTube or Instagram are more effective than Facebook in the IACM variables 'information quality', 'information credibility', 'information usefulness', 'positive buying intention with digital influencer positive information' and 'negative buying intention with digital influencer negative information'.